2018
DOI: 10.1161/jaha.117.007626
|View full text |Cite
|
Sign up to set email alerts
|

Epothilone B Benefits Nigrostriatal Pathway Recovery by Promoting Microtubule Stabilization After Intracerebral Hemorrhage

Abstract: BackgroundMany previous clinical studies have demonstrated that the nigrostriatal pathway, which plays a vital role in movement adjustment, is significantly impaired after stroke, according to medical imaging and autopsies. However, the basic pathomorphological changes have been poorly investigated to date. This study was designed to explore the pathomorphological changes, mechanism, and therapeutic method of nigrostriatal impairment after intracerebral hemorrhage (ICH).Methods and ResultsIntrastriatal injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 37 publications
5
33
0
Order By: Relevance
“…It is noteworthy that intraperitoneal administration of low doses of epothilone suppressed axonal microtubule loss and alleviated cognitive defects in a mouse model of tauopathy (Ballatore et al, 2012 ), and systemic injection of epothilone D was neuroprotective in an MPTP-induced mouse model of parkinsonism (Cartelli et al, 2013 ). Recently, we demonstrated that EpoB alleviated injury of the nigrostriatal pathway after intracerebral hemorrhage and improved motor function in a mouse model (Yang et al, 2018a ), confirming the neuroprotective effects of EpoB.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…It is noteworthy that intraperitoneal administration of low doses of epothilone suppressed axonal microtubule loss and alleviated cognitive defects in a mouse model of tauopathy (Ballatore et al, 2012 ), and systemic injection of epothilone D was neuroprotective in an MPTP-induced mouse model of parkinsonism (Cartelli et al, 2013 ). Recently, we demonstrated that EpoB alleviated injury of the nigrostriatal pathway after intracerebral hemorrhage and improved motor function in a mouse model (Yang et al, 2018a ), confirming the neuroprotective effects of EpoB.…”
Section: Introductionsupporting
confidence: 58%
“…The beam walking test was performed to assess motor coordination and was conducted according to previously described methods (Yang et al, 2018a ). A beam of 6 mm width, 1.2 m length and 60 cm height was used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epothilones act similarly but are preferred because they cross the blood-brain barrier (Ruschel et al, 2015). In a plethora of studies published over the past several years, microtubule-stabilizing drugs have been shown to augment nerve regeneration in the culture dish as well as animal models, even leading to partial recovery of function in rats with injured spinal cords (Hellal et al, 2011;Sengottuvel et al, 2011;Ruschel et al, 2015;Li et al, 2017;Ruschel and Bradke, 2018;Sandner et al, 2018;Yang et al, 2018;Yin et al, 2018). However, an independent attempt failed to achieve notable regeneration or functional recovery, with only modest improvements apparently attributable to the effects of the drugs on non-neuronal cells contributing to the glial scar (Popovich et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The study design is shown in Figure 1(a). The ICH model was established in accordance with previously described methods as shown in Figure 1(b) [15]. Mice were anesthetized with isoflurane (3% for induction and 1-1.5% for maintenance).…”
Section: Experimental Design and Intracerebral Hemorrhagementioning
confidence: 99%